Advances in non-thermal technologies for whole and minimally processed apple fruit – A review. (December 2022) - Nyamende, Nandi E.; Sigge, Gunnar O.; Belay, Zinash A.; Mphahlele, Rebogile R.; Oyenihi, Ayodeji B.; Mditshwa, Asanda; Hussein, Zaharan M.; Caleb, Oluwafemi James
Abstract: Apples are rich sources of bioactive compounds (e.g., anthocyanins, flavanols, flavonols, and antioxidant activity), and micronutrients (e.g., vitamins, zinc, and iron) that are essential for normal human body functions. These compounds in apples help to regulate immune responses and protect against chronic diseases by neutralizing and eliminating cellular free radicals. Apple fruit production is ranked second globally, which has economic implication. The conventional industry practice of using chlorine-based chemical disinfectants has been discouraged based on public health concerns, and by strict policies limiting chemical residues on fresh or minimally processed ready to eat fruit. Therefore, the aim of this review is to provide a critical assessment on the status of emerging non-thermal technologies such as cold plasma, pulsed electric fields, ozone, electrolyzed water, and edible coatings for the whole and minimally processed apple fruit industry. The influence of these non-thermal technologies on microbial decontamination, preservation of bioactive compounds, and overall quality of apples during storage is discussed. In addition, based on extensive report on various studies about non-thermal technologies for apples. This review concluded that future investigations should focus on balancing the decontamination performance of these non-thermal technologies with the preservation of essential nutritional quality attributes, providing guidance for the apple fruit industry. Highlights: Non-thermal technologies have shown efficacy as disinfectant for whole/fresh-cut apples. Electrolyzed water is an effective disinfectant with minimal impact on apple quality. Reactive species of cold plasma, ozone, and UV radiation damages bacterial cells. Edible coating showed enhanced antioxidant activities of fresh-cut apples.